Atomic sites and stability of Cs(+) captured within zeolitic nanocavities - Yoshida, Kaname (Nature Publishing Group, 2013)
Zeolites have potential application as ion-exchangers, catalysts and molecular sieves. Zeolites are once again drawing attention in Japan as stable adsorbents and solidification materials of fission products, such as (137)Cs(+) from damaged nuclear-power plants. Although there is a long history of scientific studies on the crystal structures and ion-exchange properties of zeolites for practical application, there are still open questions, at the atomic-level, on the physical and chemical origins of selective ion-exchange abilities of different cations and detailed atomic structures of exchanged cations inside the nanoscale cavities of zeolites. Here, the precise locations of Cs(+) ions captured within A-type zeolite were analyzed using high-resolution electron microscopy. Together with theoretical calculations, the stable positions of absorbed Cs(+) ions in the nanocavities are identified, and the bonding environment within the zeolitic framework is revealed to be a key factor that influences the locations of absorbed cations.